Strategies for the Voltammetric Detection of Loop-Mediated Isothermal Amplification - Jesse M. Marangoni; Kenneth K. S. Ng; Arezoo Emadi (Micromachines, 2023)
Loop-mediated isothermal amplification (LAMP) is rapidly developing into an important tool for the point-of-use detection of pathogens for both clinical and environmental samples, largely due to its sensitivity, rapidity, and adaptability to portable devices. Many methods are used to monitor LAMP, but not all are amenable to point-of-use applications. Common methods such as fluorescence often require bulky equipment, whereas colorimetric and turbidimetric methods can lack sensitivity. Electrochemical biosensors are becoming increasingly important for these applications due to their potential for low cost, high sensitivity, and capacity for miniaturization into integrated devices. This review provides an overview of the use of voltammetric sensors for monitoring LAMP, with a specific focus on how electroactive species are used to interface between the biochemical products of the LAMP reaction and the voltammetric sensor. Various strategies for the voltammetric detection of DNA amplicons as well as pyrophosphate and protons released during LAMP are presented, ranging from direct DNA binding by electroactive species to the creative use of pyrophosphate-detecting aptamers and pH-sensitive oligonucleotide structures. Hurdles for adapting these devices to point-of-use applications are also discussed.